ANALISIS RASIO PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN AKTIVITAS TERHADAP PENGEMBALIAN INVESTASI PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI PERIODE 2012-2014 - B51111148, Nurmalinda (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
The investments made by investors in the capital markets generally aim to get a return on investment in the form of dividends and capital gains. Dividends and capital gains are indicators for the increasing of the investorsâ€™ wealth as a reward for their bravery in the risk for use of the investments made.the aim of this study is to examine ratio of profitability, liquidity, leverage, and activity on investment returns. Sample of this research are manufacturing companies listed in Indonesia Stock Exchange during the period 2012 to 2014. Those companies have a positive value of Dividend Payout Ratio and have distributed dividends during the period of 2012 through 2014 and 62 companies are taken as a sample and to analyse the data, multiple linear regressions are employed. The results showed that the leverage ratio is a variable that has the highest ability and have a positive influence on investment returns. Keywords: profitability ratios, liquidity ratio, leverage ratio, activity ratio, investment return Â